Ice Wall Growth and Decay: Meteorological Analysis and Modelling. (3rd February 2015) - Gauthier, F.; Allard, M.; Hétu, B.
Abstract The growth and decay of three ice walls were surveyed and analysed during the winter of 2010–11. Ice walls form on a cliff face due to the freezing of seeping ground water: two of the studied ice walls are on north‐facing rock faces and one is on a south‐facing cliff. Models of ice wall growth and decay were developed using meteorological data collected in their immediate surroundings and checked against growth and decay rates measured by volume changes obtained from terrestrial light detection and ranging images. A complete energy balance model is proposed and compared with two other simplified models. The first one is a temperature index or freezing degree‐hours model (FDHm), and the second one is a model that combines the FDHm and the radiation heat budget (Qrad). Both models reveal that heat loss from air convection from the seeping water to the atmosphere is the dominant heat transfer flux responsible for the north‐facing ice wall growth and decay. Solar radiation also plays a major role in the melting of these ice walls. The overall evolution of the south‐facing ice wall is more dependent on the daily variation of Qrad. When the air temperature falls below 0 °C, the ice forms mostly during the night while solar radiation favours its melting during the day. Copyright © 2015 John Wiley & Sons, Ltd.